2008
DOI: 10.1213/ane.0b013e31817e7065
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Distribution of Neural Blockade by Local Anesthetics in Epidural Anesthesia and a Comparison of Lumbar Versus Thoracic Epidural Anesthesia

Abstract: The spread of sensory blockade after epidural injection of a specific dose of local anesthetic (LA) differs considerably among individuals, and the factors affecting this distribution remain the subject of debate. Based on the results of recent investigations regarding the distribution of epidural neural blockade, specifically for thoracic epidural anesthesia, we noted that the total mass of LA appears to be the most important factor in determining the extent of sensory, sympathetic, and motor neural blockade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 149 publications
1
78
1
2
Order By: Relevance
“…Thoracic epidural can reliably provide procedural anesthesia, but its limitations in these patients are that: i) the procedure is an outpatient based minor procedure; ii) dermatomal anesthesia obtained will, at times, be difficult to control as the spread of local anesthetic in the thoracic epidural space depends on a multitude of factors [11]; iii) compared to bilateral 3-level PVBs, the sympathectomy is more pronounced [12]; and iv) for it to provide postprocedural analgesia, an epidural catheter has to be inserted. SAB, though an option for procedures such as placement of percutaneous endoscopic gastrostomy tubes, would not be ideal as: i) it would cause a more significant sympathectomy and hypotension compared to bilateral 3-level PVB; ii) the duration of SAB and the anesthesia is limited (45 min to 3 hours) depending on the type of local anesthetic used; iii) it has no benefit from postoperative analgesia which can be obtained with PVBs, and iv) urinary retention and spinal headache [13] can be problematic, which can be avoided by using segmental PVBs targeting the dermatomes where the procedure would be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic epidural can reliably provide procedural anesthesia, but its limitations in these patients are that: i) the procedure is an outpatient based minor procedure; ii) dermatomal anesthesia obtained will, at times, be difficult to control as the spread of local anesthetic in the thoracic epidural space depends on a multitude of factors [11]; iii) compared to bilateral 3-level PVBs, the sympathectomy is more pronounced [12]; and iv) for it to provide postprocedural analgesia, an epidural catheter has to be inserted. SAB, though an option for procedures such as placement of percutaneous endoscopic gastrostomy tubes, would not be ideal as: i) it would cause a more significant sympathectomy and hypotension compared to bilateral 3-level PVB; ii) the duration of SAB and the anesthesia is limited (45 min to 3 hours) depending on the type of local anesthetic used; iii) it has no benefit from postoperative analgesia which can be obtained with PVBs, and iv) urinary retention and spinal headache [13] can be problematic, which can be avoided by using segmental PVBs targeting the dermatomes where the procedure would be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable factors of the level and duration of thoracic epidural anesthesia (TEA) are mainly the injection site, type and concentration of the local anesthetic administered, the use of adjuvant medications and patient characteristics especially extreme weight , age, height, pregnancy and obesity [7]. Hirabayashi establishes requirements according to age groups: 20-29 years: 1.4 mL; 30-29 years: 1.2 mL; 40-49 years: 1.0 mL; 50-59 years: 1.0 mL; 60-69 years: 0.8 mL; 70-79 years: 0.7 mL [8] these considerations are used by the author to determine the volume of local anesthetic to the introduction of epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Local distribution of anesthetic in the epidural space is more likely to proceed cephalad when the drug is injected in a low thoracic site (T6-L1). 18 Additionally, a patient's body position at the time of injection or infusion may play a role, particularly in the unilateral distribution. 12,14,16 In our case, normal results on the neurological examination suggested that acute stroke was not responsible for the signs and symptoms in question.…”
Section: Discussionmentioning
confidence: 99%